Electroweak production of two jets in association with a Z boson in proton-proton collisions root s =13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
A measurement of the electroweak (EW) production of two jets in association with a Z boson in protonproton collisions at √s = 13 TeV is presented, based on data recorded in 2016 by the CMS experiment at the LHC corresponding to an integrated luminosity of 35.9 fb–1. The measurement is performed in the jj final state with including electrons and muons, and the jets j corresponding to the quarks produced in the hard interaction. The measured cross section in a kinematic region defined by invariant masses m > 50 GeV, mjj > 120 GeV, and transverse momenta pTj > 25 GeV is σEW(jj) = 534 ± 20 (stat) ± 57 (syst) fb, in agreement with leading-order standard model predictions. The final state is also used to perform a search for anomalous trilinear gauge couplings. No evidence is found and limits on anomalous trilinear gauge couplings associated with dimension-six operators are given in the framework of an effective field theory. The corresponding 95% confidence level intervals are −2.6 < cWWW /Λ2 < 2.6 TeV−2 and −8.4 < cW /Λ2 < 10.1 TeV−2. The additional jet activity of events in a signal-enriched region is also studied, and the measurements are in agreement with predictions.